Efeitos do probiótico Saccharomyces boulardii na morfologia, função e modulação autonômica cardiovascular em camundongos diabéticos - Brandão, Ana Beatriz Pereira [UNIFESP] (2017)
Diabetic cardiomiopathy (CMPD) is a cardiac muscle disease, caused by diabetes mellitus (DM) and it is not related with vascular or valvular pathologies nor with systemic arterial hypertension. It is associated with the increase of collagen deposition, cardiac concentration of triglycerides and cholesterol, as well as the activation of the inflammation and reduction of nitric oxide (NO) bioavailability. Saccharomyces boulardii (S. boulardii) is a probiotic effect microorganism capable of modulating the innate and adaptive immune system, reducing pro-inflammatory and activating anti-inflammatory responses. The objective of this study was to analyze the influence of S. boulardii on the development of metabolic and cardiovascular changes induce by DM, evaluating the morphology, systolic and diastolic functions, heart rate (FC) and blood pressure (PA) variability, and cytokine and NO concentration in mice cardiac muscle. Male mice C57BL/6, received a single intraperitoneal injection of streptozotocin (STZ) (150mg/kg), and after 5 days, the blood glucose was evaluated. It was considered diabetics the animals with blood glucose ≥ 250 mg/dl, and they were distributed in four experimental groups (n= 6-12/group): control (C), diabetic (DM), control treated with probiotic (CSb) and diabetic treated with probiotic (DMSb). The animals of treated groups received 300μl of S. boulardii (0,5x108 colony forming units –CFU/ml of yeast) by gavage, daily, during 8 weeks. In the last week of treatment, the water and food intake, urinary and fecal excretion of the animals were evaluated. The animals were submitted to Doppler echocardiography and to implantation of the carotid catheter for direct recording of BP, in the eighth week of treatment. At the end of the experimental protocol the animals were killed by decapitation and blood and cardiac tissue were collected for biochemical and histological analyzes. Diabetic animals presented typical symptoms associated with DM, such as hyperglycemia, polyuria and loss of body mass, as well as lipid dysfunction. The probiotic reduced glycemia and triglycerides plasma concentration. In addition, diabetic animals presented reduction of heart mass, increased tissue concentration of IL-6 associated with reduction of cardiac concentration of IL-10 and NO. On the other hand, the treatment of diabetic animals with probiotic reduced the cardiac concentration of IL-6, and increased that of IL-10 and NO. In addition, treatment with S. boulardii exerted a beneficial effect on autonomic control and the systolic and diastolic dysfunction associated with DM, increasing the variability of HR and SBP, as well as the power of the LF low frequency component of SBP. Therefore, the results of the present study show that treatment with S. boulardii attenuates the development of CMPD through metabolic control, modulation of the inflammatory process as well as the improvement of autonomic control, suggesting this as an additional therapy for the treatment of cardiac changes induced by DM.